2015
DOI: 10.1097/icu.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser refractive surgery

Abstract: SMILE is a promising new surgery for refractive error correction. Prospective and retrospective studies of SMILE have shown that results of SMILE are similar to FS-LASIK. With advances in femtosecond laser technology, SMILE may gain greater acceptance in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 43 publications
(33 reference statements)
1
10
1
Order By: Relevance
“…Our findings are similar to reviews comparing SMILE and FS-LASIK conducted by Lee et al and Zhang et al[ 6 , 41 ]. However, Miao et al’s meta-analysis reported a dissimilar finding that corneal sensitivity in the SMILE group is better than the FS-LASIK group during the first three postoperative months, but similar at six months after surgery[ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to reviews comparing SMILE and FS-LASIK conducted by Lee et al and Zhang et al[ 6 , 41 ]. However, Miao et al’s meta-analysis reported a dissimilar finding that corneal sensitivity in the SMILE group is better than the FS-LASIK group during the first three postoperative months, but similar at six months after surgery[ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Corneal refractive surgery, such as femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE), has emerged as having good efficacy, predictability, safety, and stability for surgical correction of low, moderate, and high myopia 24…”
Section: Discussionmentioning
confidence: 99%
“…The availability of femtosecond technique has helped to promote microkeratome-free refractive surgeries 1. Both femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) have become the preferred surgery of choice for an increasing number of surgeons who perform refractive surgeries 2–5…”
mentioning
confidence: 99%